MODEL PEMBELAJARAN AKUNTANSI UNTUK MENINGKATKAN KOMPETENSI MAHASISWA - Titisari, Kartika Hendra; Wijayanti, Anita; Chomsatun, Yuli (Buletin Studi Ekonomi; VOL.18.NO.2.AGUSTUS 2013. (PP 85-190), 2014)
Abstract : Accounting Learning Model to Increase Student Competence. Accounting is one area that is not enough science learned just from the theory, but it will be easier to understand of the science area practice of accounting for real. The accounting practicum development of teaching materials is one of the efforts to improve student competence. It is assumed that with the model of appropriate learning and teaching package models that describe real conditions, can improve mastery of the material and ultimately improve student competence.The objectives of this research is to develop a model accounting package practicum learning as a strategy to improve the quality of learning financial accounting and tax accounting to increase student competence. This study will answer the question of how learning models and models of learning packages appropriate accounting practice in accounting courses. Research design using the design research and developed or Research and Development (R & D). Development to follow Instructional Development Model (MPI) the procedur. The development of the role of accounting in the industrial world demands competency appropriate user needs graduates. The results of the concept model of learning and teaching practicum accounting package. The results still have to go through testing to be in generalization.
Keywords: Accounting, Learning, Model